Sintilimab-Induced Myocarditis Overlapping Myositis in a Patient With Metastatic Thymoma: A Case Report - Yang, Zi-xuan; Chen, Xuan; Tang, Si-qi; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2021)
Although immune checkpoint inhibitor (ICI)-related myocarditis has been widely discussed, a lot of gaps and challenges in its clinical course and rational intervention remain elusive. We present the case of a 33-year-old man with a history of metastatic thymoma who developed dyspnea and muscle weakness one month after the first dose of Sintilimab. He was asymptomatic but found to have a mild elevation of troponin-T and a moderate increase of creatine kinase 20 days after the infusion. Although the scheduled second dose was deferred, he developed dyspnea, left bundle branch block and left ventricular enlargement that suggestive of Grade 3 ICI-related myocarditis, complicated with myositis/ myasthenia gravis 10 days later. Fortunately, his response to intensive immunosuppressive therapy was good.